Kulturwissenschaftliche Germanistik versus interkulturelle Germanistik - Überlegungen zu Entwicklungen des Faches in den 70er und 80er Jahren - Papiór, Jan (Studia Germanica Posnaniensia, 2018)
The external impulse for the formulation of these considerations became the setting up of the Department of Culture of German-speaking Countries at the Institute of German, Adam Mickiewicz University in Poznań in the academic year 1987-88. Along with the establishing of the department the hitherto structure of German studies in Poznań has been extended: history of literature, linguistics, methodology, and study of culture of German-speaking countries, thus creating for the studies a possibility of writing diploma works in the field of the specialization which is immanently contained from the very start of every neophilology. These considerations are focussed on the determinants of German studies as a discipline of one's native and foreign language: what is important is the position in the field of ones' own culture, and in the second case the double context towards the ever present one's own culture as placed against the foreign culture. An attempt is made at showing other (foreign) cultural perspectives, arising during research work, studies and teaching of another culture. This look shows the fact that the history of Europa has always been an intercultural and interpolitical phenomenon. Considerations show the function and meaning of the context of one's own culture in the research, studying and teaching of foreign culture. The most important of the six theses formulated by the author at the end of the article claims that what we attempt at in the research and teaching process of foreign philology is to form a cultural competence which uses structures of dialogue.